Empirically Tested Health Literacy Frameworks - Joycelyn Cudjoe; Sabianca Delva; Mia Cajita; Hae-Ra Han (SLACK Incorporated, 2020)
BACKGROUND: Health literacy is a significant determinant of health behaviors, but the pathways through which health literacy influences health behaviors are not completely clear nor consistent. The purpose of this systematic review is to critically appraise studies that have empirically tested the potential pathways linking health literacy to health behavior. METHODS: We performed searches of the electronic databases PubMed, Embase, and CINAHL to identify studies that proposed a conceptual framework and empirically tested the proposed mechanism through which health literacy influences certain health behaviors. Twenty eligible studies were included for analysis. KEY RESULTS: The 20 studies addressed various health behaviors: chronic disease self-management (n = 8), medication adherence (n = 2), overall health status (n = 4), oral care (n = 1), cancer screening (n = 1), shared decision-making (n = 1), health information sharing (n = 1), physical activity and eating behaviors (n = 1), and emergency department visits (n = 1). Most studies were conducted in the United States (n = 13) and used a cross-sectional design (n = 15). The Short Test of Functional Health Literacy in Adults was commonly used to assess health literacy levels. Selection of variables and their operationalization were informed by a theoretical model in 12 studies. Age, gender, race/ethnicity, and insurance status were reported antecedents to health literacy. The most commonly tested mediators were self-efficacy (n = 8) and disease knowledge (n = 4). Fit indices reported in the studies ranged from acceptable to excellent. DISCUSSION: Current evidence supports self-efficacy as a mediator between health literacy and health behavior. Further research is needed to identify how health literacy interplays with known psychosocial factors to inform people's use of preventive care services. Future studies should include more disadvantaged populations such as immigrants with high disease burden and those with low health literacy. Theory-based, empirically tested health literacy models can serve as the conceptual basis for developing effective health interventions to improve health behaviors and ultimately decrease the burden of disease in such vulnerable populations. [HLRP: Health Literacy Research and Practice. 2020;4(1):e21-e44.] PLAIN LANGUAGE SUMMARY: This review systemically compiles, and critically appraises 20 existing studies that test conceptual frameworks that propose potential pathways through which health literacy affects health behaviors. The findings from this review can help inform the development of health literacy-focused interventions to improve the health behaviors of populations with disease burdens.